The Effect of Pediococcus pentosaceus on Stool Frequency, TNF-α Level, Gut Microflora Balance in Diarrhea-induced Mice - Yuliawati Yuliawati; Yusri Dianne Jurnalis; Endang Purwati; Gustina Lubis (The Indonesian Society for Digestive Endoscopy, 2012)
Background: Enteropathogenic Escherichia coli (EPEC) are pathogenic microorganisms causing inflammation and imbalanced gut microflora that may result in diarrhea. Pediococcus pentosaceus (P. pentosaceus) isolated from “dadih” (milk curd) are used as probiotics containing lactic acid bacteria (LAB), which are useful to improve the balance of intestinal microflora and inhibit the growth of pathogenic microorganisms. This study was aimed to recognize the effect of P. pentosaceus supplementation on stool frequency, tumor necrosis factor-α (TNF-α) and gut microflora balance in experimental mice with EPEC-induced diarrhea. Method: The study was conducted in 60 white mice (Mus muscullus) at Biomedical Laboratory, Biotechnology/Production and Animal Husbandry Technology Institute, University of Andalas, Padang in April 2012. The frequency of stool, TNF-α level and microflora balance of the mice were measured before and after the EPEC-induced diarrhea and following the administration of antibiotics. Statistical analysis was performed using ANOVA and Duncan test. Results: The highest mean stool frequency was found in positive control group, i.e. 55 times, which was reduced significantly after 12-hour P. pentosaceus supplementation in a dose of 2 x 108 cfu/g into 18 times. The mean TNF-α level in positive control group was 128.17 pg/mL that lowered significantly to 48.0 pg/mL. The highest mean total number of LAB was 97.0 x 107 cfu/g, which was significantly different from positive control group of 7 x 107 cfu/g. Conclusion: P. pentosaceus supplementation in a dose of 2 x 108 cfu/g may reduce the stool frequency, lower TNF-α and improve the gut microflora balance following 12-hour supplementation in diarrhea-induced mice. Keywords: Pediococcus pentosaceus, TNF-α, diarrhea, EPEC, gut microflora